Positive Emotions and Entrepreneurial Intention: The Mediating Role of Entrepreneurial Cognition - Chen, Ben-Song; Yuan, Chih-Hung; Yin, Bin; Wu, Xiao-Zhi (Frontiers in Psychology, 2021)
Under the background of "mass entrepreneurship and innovation," entrepreneurship and innovation for college students not only alleviates the current social employment pressure but sets off the upsurge of their entrepreneurship. It is a significant field to research the entrepreneurial intention of undergraduates as potential entrepreneurs, which covers the study of entrepreneurial intention from the perspective of personal traits and entrepreneurial cognition. This article studies entrepreneurial intention from two aspects: irrational positive emotions and rational entrepreneurial cognition, which aims to reveal the mechanism of positive emotions and entrepreneurial cognition on entrepreneurial intention. After investigating 288 college students participating in entrepreneurial competitions, establishing structural equations, and using SmartPLS software for data analysis, the research result showed that positive emotions significantly positively impact the three scripts of entrepreneurial cognition: arrangement scripts, willing scripts, and ability scripts. The arrangement, willing, and ability scripts positively influence entrepreneurial intention, while positive emotions do not affect entrepreneurial intention. Arrangement scripts and ability scripts have a full mediating effect between positive emotions and entrepreneurial intention. Based on these findings, we provide suggestions for the government and society, schools and individual students on innovation and entrepreneurship.